Analisis Pengaruh Inflasi, Tingkat Pendidikan, Angkatan Kerja, dan Upah Minum Terhadap Ketimpangan Distribusi Pendapatan di Provinsi Jawa Timur - Lailia Ayu Ramadhani; Kiki Asmara (Al-Buhuts, 2024)
The objective of this study is to examine how income distribution inequality in East Java is influenced by factors such as inflation, education level, labor force participation, and minimum wage. use SPSS 25 program for multiple regression analysis. Primary data utilized here comes from the Central Bureau of Statistics (BPS) and spans the years 2010–2022. This study found that income distribution inequality in East Java Province is affected by inflation, education level, labor force participation, and minimum wage all at once. Income distribution inequality in East Java Province is partially affected by inflation, which has a positive but insignificant effect. The effect of education level is negative and significant, while the effect of labor force is negative and insignificant. The effect of minimum wage is positive and significant.